Randomly stacked open cylindrical shells as functional mechanical energy absorber - Sano, Tomohiko G.; Hohnadel, Emile; Kawata, Toshiyuki; Métivet, Thibaut; Bertails-Descoubes, Florence (Communications materials, 2023)
Structures with artificially engineered mechanical properties, often called mechanical metamaterials, are interesting for their tunable functionality. Various types of mechanical metamaterials have been proposed in the literature, designed to harness light or magnetic interactions, structural instabilities in slender or hollow structures, and contact friction. However, most of the designs are ideally engineered without any imperfections, in order to perform deterministically as programmed. Here, we study the mechanical performance of randomly stacked cylindrical shells, which act as a disordered mechanical metamaterial. Combining experiments and simulations, we demonstrate that the stacked shells can absorb and store mechanical energy upon compression by exploiting large deformation and relocation of shells, snap-fits, and friction. Although shells are oriented randomly, the system exhibits statistically robust mechanical performance controlled by friction and geometry. Our results demonstrate that the rearrangement of flexible components could yield versatile and predictive mechanical responses. Mechanical metamaterials are artificially designed structures with tunable behavior, typically obeying precisely programmed dynamics. Here, a metamaterial based on randomly stacked flexible cylindrical shells provides a disordered yet statistically robust and controllable structure for mechanical energy dissipation and storage.